Identifikasi Faktor Penyebab Perilaku Merokok Pada Mahasiswi Usia Dewasa Awal : Nur Maghfira Nisza, Rohmah Rifani, Eka Sufartianinsih Jafar - Maghfira Nisza, Nur; Rifani, Rohmah; Sufartianinsih Jafar, Eka (Fakultas Psikologi Universitas Bhayangkara Jakarta Raya, 2024)
Smoking behavior is a behavior that can endanger health, but its users are increasing. Smoking behavior is often found in adolescence, but it is not uncommon for someone who has entered early adulthood, which is caused by several internal or external factors. This research uses a qualitative method with a phenomenological study approach, to see how conscious experiences are and how to interpret these experiences using in-depth interview methods. There were three respondents in this study, with different backgrounds. The results of this study identified that the causes of female students smoking were due to external and internal factors, where external factors were due to their friendship environment, family environment, and advertising factors, while internal factors were due to their own desires, being curious about the taste of cigarettes, feeling pressured by the situation, and lacking Get attention from both parents. Apart from that, for the positive effects, it was found that by smoking, female students get the effect of being calm, relaxed, more focused, which makes the user feel cool. Meanwhile, the negative effects were found to be that smoking can cause an addictive effect and have lasting dangerous impacts on oneself and the people around them, as well as getting a negative label from the surrounding environment, especially for women who smoke.